2019
DOI: 10.1002/cncr.32488
|View full text |Cite
|
Sign up to set email alerts
|

Risk of venous thromboembolism in patients with non‐Hodgkin lymphoma surviving blood or marrow transplantation

Abstract: Background Patients with non‐Hodgkin lymphoma (NHL) have an increased risk of venous thromboembolism (VTE), particularly when they are receiving treatment. Blood or marrow transplantation (BMT) is recommended for relapsed/refractory NHL, and the risk of VTE after these patients undergo BMT is uncertain. Methods Patients with NHL who survived 2 years or longer after BMT were surveyed for long‐term health outcomes, including VTE. The median follow‐up was 8.1 years (interquartile range, 5.6‐12.9 years). The risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
(40 reference statements)
0
7
3
1
Order By: Relevance
“…and V.D.S.). Of the 25 studies included, 12 studies were retrospective single-center studies [7,8,[10][11][12][13][14][15][16][17][18][19], two studies were retrospective multicenter trials [20,21], two pooled analysis of clinical trials [9,22], two meta-analyses [23,24], two analyses of patients [25,26] and three analyses of population-based registries [27][28][29], and two prospective single-center studies [6,30] ( Table 1). Four additional studies were identified by cross-referencing in the 21 published reports.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…and V.D.S.). Of the 25 studies included, 12 studies were retrospective single-center studies [7,8,[10][11][12][13][14][15][16][17][18][19], two studies were retrospective multicenter trials [20,21], two pooled analysis of clinical trials [9,22], two meta-analyses [23,24], two analyses of patients [25,26] and three analyses of population-based registries [27][28][29], and two prospective single-center studies [6,30] ( Table 1). Four additional studies were identified by cross-referencing in the 21 published reports.…”
Section: Methodsmentioning
confidence: 99%
“…and V.D.S.). Of the 25 studies included, 12 studies were retrospective single-center studies [7,8,[10][11][12][13][14][15][16][17][18][19], two studies were retrospective multicenter trials [20,21], two pooled analysis of clinical trials [9,22], two meta-analyses [23,24], two analyses of patients [25,26] and three analyses of population-based registries [27][28][29], and two prospective single-center studies [6,30] (Table 1). Patients included into these studies were identified by institutional databases in 14 studies [7,8,[10][11][12][13][14][15][16][18][19][20][21]30], by the local hospital discharge registry in one study [17], by cancer registries in four studies (California Cancer Registry [27], VA Cancer registry [25], Swedish cancer registry [29], Danish lymphoma database [28]), by clinical trial registries in five ...…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations